1,000 inventions & discoveries - Bridgman, Roger Francis 1940- (New York DK Pub, 2002)
Summarizes 100 notable inventions and discoveries of ancient and modern times, from 3,000,000 B.C. to the beginning of the twenty-first century A.D
Includes bibliographical references (p 256) and index
1 9 10
Keywords: Encyclopedias